Effects of Metabolic Dysfunction–Associated Steatohepatitis in Alertness, Associative Learning, and Astrocyte Density - Sara G. Higarza; Marina De Antón‐Cosío; Candela Zorzo; Jorge L. Arias; Natalia Arias (Brain and Behavior)
ABSTRACT Purpose Metabolic dysfunction–associated steatohepatitis (MASH) is a prevalent disease caused by high fat and high cholesterol intake, which leads to systemic deterioration. The aim of this research is to conduct a psychobiological exploration of MASH in adult male rats. Methods Subjects who were administered a high‐fat and high‐cholesterol diet for 14 weeks. Then, we assessed the acoustic startle response and alertness through the prepulse inhibition paradigm as well as the associative learning by the use of the passive avoidance test. Also, we explored the astrocyte density in the prefrontal cortex and hippocampus. Results Our results showed that, whereas the MASH group did not display an impaired associative learning, a lower exploration rate was found in this group. Moreover, a reduced prepulse inhibition was found in these subjects in the case of the weaker and closer‐to‐the‐stimulus prepulse, which indicates a mild alteration in this process. No differences were found in astrocyte density in the MASH group in comparison with controls. Conclusion MASH seems to be linked with cognitive dysfunction. Further research is needed to elucidate the pathway involved in this disease and its underlying mechanism, as well as the potential implication in human health.